PENGEMBANGAN E-LKPD BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Widiyanti, Tia; Fitrotun Nisa, Ana (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study aims to find out the characteristics of e-LKPD in the subjects of natural science (IPA) based on the scientific approach, the validation, and the effectiveness of the developed e-LKPD. This research used Research and Development (R&D) method. In collecting the data, the researcher used questionnaires, observation, interviews, the result of the learning process, and documentation. The data analysis used descriptive statistics analysis. Development of e-LKPD includes 9 stages of development. The subject testing was conducted on 24 students of fifth-grade students of SD N 2 Surokarsan Yogyakarta. The results of this study are the characteristics of e-LKPD in the subjects of natural science (IPA) based on a scientific approach using 5M components. The validation of e-LKPD product of the expert validator material result is obtained an overall average of 3.34 in the very good category, the validation of language expert has obtained an overall average of 3.25 in the very good category, the validation of media expert has obtained an overall average of 3.66 in the very good category, and the validation of the teacher of fifth-grade is obtained an overall average of 3.83 in the very good category. The practicality of the e-LKPD product showed a positive response with an average percentage of 81,1% and 82,3%. The effectiveness of e-LKPD is measured by the student result of the learning process who gets a score of 82,81.